Piano labs in music education - Holland, Marianne, 1834-1920.; Doughty, Ray.; Folks, Steve; South Carolina Educational Television Network (Columbia, S.C. : S.C. ETV, 1989)
Marianne Holland discusses group piano instruction.
VHS format.
Clint Bryson, Don Mills, Robert Rothstein, cameras ; Elaine Cooper, editor.
Marianne Holland, instructor ; Ray Doughty, series host.
Recorded Sept. 14, 1989.
Keywords: Piano -- Methods -- Group instruction